(untitled) (Raparin Journal of Humanities (RJH), 2024)
Youth migration is a phenomenon in most developed and poor societies, as well as societies that suffer from lack of job opportunities, adequate rights, corruption, political and security instability The aim of this study is to identify the reasons for the migration of young people abroad in the Kurdistan Region for nearly a decade, especially the migration of young people Illumination of migration theories. The most important results of this study are: Lack of adequate job opportunities and adequate rights is one of the reasons for youth migration, and expect another reason for migration among young people, migrant networks through social networks have a great impact on youth migration Another reason for young people to migrate is to increase their family income.